Bites by the saw-scaled or carpet viper (Echis carinatus): trial of two specific antivenoms. - Warrell, D; Davidson, N; Omerod, L; Pope, H; Watkins, B; Greenwood, B; Ried, H (1974)
Echis carinatus is the most important cause of morbidity and mortality from snake bite in Nigeria and in many other parts of the world. Forty-six patients with systemic poisoning by this snake were given echis antivenom made either by the South African Institute for Medical Research (S.A.I.M.R.) or by Behringwerke (North and West African polyvalent antivenom). A simple test of blood coagulability was used to assess whether an adequate neutralizing dose of antivenom had been given. An average of 15.2 ml S.A.I.M.R. antivenom restored normal coagulability permanently in all 23 patients in one group, but in the other group receiving an average dose of 37.9 ml Behringwerke antivenom normal clotting resulted in only 18 out of 23 patients. Local tissue swelling was similar in both groups, but local necrosis occurred in three patients treated with Behringwerke antivenom and in none given S.A.I.M.R. antivenom.